Applied Multivariate Statistical Analysis - HRardle, Wolfgang Karl; Simar, Léopold (Springer, 2015)
The fourth edition of this book on Applied Multivariate Statistical Analysis offers a new sub-chapter on Variable Selection by using least absolute shrinkage and selection operator (LASSO) and its general form the so-called Elastic Net. All pictures and numerical examples have been now calculated in the (almost) standard language R & MATLAB. The code for each picture is indicated with a small sign near the picture, e.g. MVAdenbank denotes the corresponding quantlet for reproduction of Fig. 1.9, where we display the densities of the diagonal of genuine and counterfeit bank notes. We believe that these publicly available quantlets (see also http://sfb649.wiwi.hu-berlin.de/quantnet/) create a valuable contribution to distribution of knowledge in the statistical science. The symbols and notations have also been standardised. In the preparation of the fourth edition, we received valuable input from Dedy Dwi Prastyo, Petra Burdejova, Sergey Nasekin and Awdesch Melzer. We would like to thank them.